A concepção de mudança radical na teoria crítica de Herbert Marcuse - Aquino, John Karley de Sousa (2022)
In his writings, Herbert Marcuse was concerned with ensuring a solid philosophical basis for Marxism, in order to justify the revolutionary process and at the same time think of the revolution as something deeper than changes in the economic foundations of society. For him, the revolution would imply an effective change in human sociability, it would drive a new way of being of things and a new anthropology, with new meanings and in a new relationship of the subject with objective reality, in short, it would be what he defines as a radical change. This thesis aims to explain the notion of radical change that permeates the Critical Theory of society by the philosopher Herbert Marcuse. The work of the frankfurtian intellectual is analyzed, focusing on the writings after the 1940s, trying to identify the concept that is dispersed in his vast bibliographic production. It is concluded that Marcuse's philosophy has a commitment to practice and constantly tries to find alternatives to the status quo, thinking of tactics and strategies that allow the radical opposition to overcome the capitalist system, no matter how solid and stable it seems to be.